How to Look for Compounds: Predictive Screening and in situ Studies in Na−Zn−Bi System. Issue 64 (12th October 2021) - Gvozdetskyi, Volodymyr; Wang, Renhai; Xia, Weiyi; Zhang, Feng; Lin, Zijing; Ho, Kai‐Ming; Miller, Gordon; Zaikina, Julia V.
Abstract: Here, the combination of theoretical computations followed by rapid experimental screening and in situ diffraction studies is demonstrated as a powerful strategy for novel compounds discovery. When applied for the previously "empty" Na−Zn−Bi system, such an approach led to four novel phases. The compositional space of this system was rapidly screened via the hydride route method and the theoretically predicted NaZnBi (PbClF type, P 4/ nmm ) and Na11 Zn2 Bi5 (Na11 Cd2 Sb5 type, P 1 ‾ ) phases were successfully synthesized, while other computationally generated compounds on the list were rejected. In addition, single crystal X‐ray diffraction studies of NaZnBi indicate minor deviations from the stoichiometric 1 : 1 : 1 molar ratio. As a result, two isostructural (PbClF type, P 4/ nmm ) Zn‐deficient phases with similar compositions, but distinctly different unit cell parameters were discovered. The vacancies on Zn sites and unit cell expansion were rationalized from bonding analysis using electronic structure calculations on stoichiometric "NaZnBi". In‐situ synchrotron powder X‐ray diffraction studies shed light on complex equilibria in the Na−Zn−Bi system at elevated temperatures. In particular, the high‐temperature polymorph HT ‐Na3 Bi (BiF3 type, Fm 3 ‾ m ) was obtained as a product of Na11 Zn2 Bi5 decomposition above 611 K. HT ‐Na3 Bi cannot be stabilized at room temperature by quenching, and this type of structure was earlier observed in the high‐pressure polymorph HP ‐Na3 Bi above 0.5 GPa. The aforementioned approach of predictive synthesis can be extended to other multinary systems. Abstract : A structure prediction algorithm was used to assess the stability of the ternary compounds in the Na−Zn−Bi system followed by rapid experimental screening via the hydride synthesis route and in situ synchrotron X‐ray diffraction studies. Such a synergistic approach has yielded four new compounds in the previously "empty" Na−Zn−Bi system. The advanced electronic structure calculation for the synthesized compounds were performed to rationalize the experimentally observed non‐stoichiometry, while in situ powder X‐ray diffraction revealed the high‐temperature polymorphism.